Analysis of Circular Economy Potential in Waste Management: Operational Efficiency and Economic Impact at TPS3R Bungo Lintas - Yulda, Apri; Nurcihikita, Tiara; Efriyandi, Yogi (Yayasan Riset dan Pengembangan Intelektual, 2024)
The circular economy-based waste management at TPS3R (Waste Management Center with Reduce, Reuse, Recycle Approach) offers significant potential in reducing waste and creating economic value. This study analyzes the potential of the circular economy in waste management at TPS3R Bungo Lintas, focusing on operational efficiency and economic impact. The study employs a mixed-methods approach with an explanatory sequential design, where quantitative data is analyzed first to measure operational efficiency and economic impact, followed by qualitative interviews to deepen the quantitative findings. The results show that TPS3R’s operational efficiency increased from 58.33% in 2021 to 61.11% in 2023, exceeding the minimum waste reduction target of 50%. The economic impact is measured through a cost-benefit ratio (BCR), showing a value greater than 1, with a net value of Rp4,345,000.00, indicating that TPS3R provides positive economic benefits. The challenges faced include a lack of public understanding of the circular economy concept, limited managerial knowledge of TPS3R operations, waste processing technology, and stakeholder policy support. Nevertheless, the potential for economic development through expanding community participation, selling recycled products, and the wider adoption of technologies such as maggot bioconversion offers new opportunities to increase TPS3R’s revenue. These findings highlight the importance of policy support, technology, public education, and improved management of TPS3R to strengthen the sustainability of the circular economy model at the local level.